(untitled) (Uzbek Scholar Journal, 2022)
Tourism is one of the fastest growing industries in the world and is also one of the best ways to boost a country’s economy. With more and more destinations realizing this and seeking to attract more tourists, the industry is becoming increasingly competitive. This is why it’s now more important than ever to ensure that your marketing strategy is up to scratch.